Sanitary-ware factories: heat recovery strategies to optimize energy and water consumption. (January 2019) - Cuviella-Suárez, Carlos; Colmenar-Santos, Antonio; Borge-Diez, David; Rosales-Asensio, Enrique
Abstract: Sanitary-ware manufacturing has a specific particular configuration of energy consumption from the thermal point of view. Heat requirements and temperature levels through the different sub-processes in the manufacturing sequence are distributed in such a way that a proper network of recovered heat can save up to 1/3 of the primary energy consumption of the factory. A half of the total thermal requirement is devoted to fire the ware along a tunnel kiln that exhausts ¾ of this heat through the exhausting and cooling stacks at a temperature a proper temperature level to be recovered in the rest of common thermal processes as drying or heating. On the other hand, the great water consumption to flush resin molds can be saved by a multi-effect distillation treatment fed with recovered heat. Instead of rejecting it with solved salts, a combined power plant optimally sized can be coupled to match both, electrical and thermal consumptions allowing for extra heat to distillate the flushing water. This research shows how sanitary-ware manufacturing can be re-engineered to save most of the water and 31 percentof primary energy